(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2018)
A simple, accurate, isocratic stability indicating RP‐HPLC method was developed for the determination of cefepime and amikacin in Pure and its pharmaceutical formulations. The method consists of methanol: acetonitrile:acetate buffer 75:20:05 (v/v) mobile phase at pH 5.1 with C18 column as stationary phase. The flow rate and detection wave length were 1.0 mL/min and 212 nm respectively. The linearity range for the method was found to be 2.5-25 µg/mL for amikacin and 10-100 µg/mL cefepime respectively. The developed method was validated as per ICH guidelines and the results of all the validation parameters were well within their acceptance values. Also the forced degradation studies were conducted with standard drugs. Degradation products formed during the different stress conditions were separated from both drugs. This validated method was applied for the simultaneous estimation of cefepime and amikacin in commercially available formulation sample.